2017
DOI: 10.15294/biosaintifika.v9i3.9670
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production of Gynura procumbens Adventitious Roots in Different Type of Liquid Culture

Abstract: <p class="IsiAbstrakIndo"><em><span lang="EN-GB">Gynura procumbens</span></em><span lang="EN-GB"> has a potency to produce raw material for pharmaceutical industry. Liquid culture systems have significant effects on multiplication rates of organ, so the propagation technology to increase biomass of this plant or organ using the liquid culture system was necessary. This research was conducted to compare biomass production of adventitious roots of </span><em><sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The bubbles of the balloon-type bubble bioreactor (BTBB) lessen the shear forces; therefore, this kind of bioreactor is suitable for culturing plant organs. However, the study conducted by Manuhara et al [141] showed that the highest biomass production (fresh weight) was found in the balloon-type bubble bioreactor (13.1-fold higher than the initial explant), followed by that in the temporary immersion system bioreactor (5.12-fold higher than the initial explant) and shake flask (3.9-fold higher than the initial explant), respectively [141].…”
Section: Adventitious Root Culture In Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bubbles of the balloon-type bubble bioreactor (BTBB) lessen the shear forces; therefore, this kind of bioreactor is suitable for culturing plant organs. However, the study conducted by Manuhara et al [141] showed that the highest biomass production (fresh weight) was found in the balloon-type bubble bioreactor (13.1-fold higher than the initial explant), followed by that in the temporary immersion system bioreactor (5.12-fold higher than the initial explant) and shake flask (3.9-fold higher than the initial explant), respectively [141].…”
Section: Adventitious Root Culture In Bioreactorsmentioning
confidence: 99%
“…In Gynura procumbens, the production of root biomass was compared to different liquid cultures (shake flask, balloon-type bubble bioreactor and temporary-immersion bioreactor). It has been reported that some problems in liquid culture, such as asphyxia and hyperhydricity, were observed during the low oxygen and submerged conditions in the medium [141]. However, to overcome this problem, a temporary immersion system bioreactor and balloon-type bubble bioreactor was applied.…”
Section: Adventitious Root Culture In Bioreactorsmentioning
confidence: 99%
“…Some authors have monitored the effect of different sucrose concentrations in the culture substrate on biomass production. In particular, Curcuma zedoaria, Zingiber zerumbet, Gynura procumbens, and Bletilla striata have showed that a higher concentration of sugar improves the performance of explants [52,62,73], whereas a significant increase in shoots number (13.05) of Bambusa vulgaris was noted in TIS with a sucrose-free medium [51].…”
Section: Medium Composition and Biomass Productionmentioning
confidence: 99%